Molecular Characterization and Regulation of the aguBA Operon, Responsible for Agmatine Utilization in Pseudomonas aeruginosa PAO1 - Nakada, Yuji (American Society for Microbiology, 2001)
Pseudomonas aeruginosa PAO1 utilizes agmatine as the sole carbon and nitrogen source via two reactions catalyzed successively by agmatine deiminase (encoded by aguA; also called agmatine iminohydrolase) and N-carbamoylputrescine amidohydrolase (encoded by aguB). The aguBA and adjacent aguR genes were cloned and characterized. The predicted AguB protein (M(r) 32,759; 292 amino acids) displayed sequence similarity (≤60% identity) to enzymes of the β-alanine synthase/nitrilase family. While the deduced AguA protein (M(r) 41,190; 368 amino acids) showed no significant similarity to any protein of known function, assignment of agmatine deiminase to AguA in this report discovered a new family of carbon-nitrogen hydrolases widely distributed in organisms ranging from bacteria to Arabidopsis. The aguR gene encoded a putative regulatory protein (M(r) 24,424; 221 amino acids) of the TetR protein family. Measurements of agmatine deiminase and N-carbamoylputrescine amidohydrolase activities indicated the induction effect of agmatine and N-carbamoylputrescine on expression of the aguBA operon. The presence of an inducible promoter for the aguBA operon in the aguR-aguB intergenic region was demonstrated by lacZ fusion experiments, and the transcription start of this promoter was localized 99 bp upstream from the initiation codon of aguB by S1 nuclease mapping. Experiments with knockout mutants of aguR established that expression of the aguBA operon became constitutive in the aguR background. Interaction of AguR overproduced in Escherichia coli with the aguBA regulatory region was demonstrated by gel retardation assays, supporting the hypothesis that AguR serves as the negative regulator of the aguBA operon, and binding of agmatine and N-carbamoylputrescine to AguR would antagonize its repressor function.